Comparative Study of Conventional Cantilever Wall and Mechanically Stabilized Earth Wall for Slope Failure Remediation - Johan P. H. Waskito; Danang S. Raharja (Journal of Civil Engineering, 2023)
Slope failure is caused by many factors, mainly high rainfall, especially in a tropical country like Indonesia. Many solutions have been expanded to do remediation of slope failure. However, establishing the best solution method is difficult because of many geotechnical challenges and different situations at the site. In addition, fast rate construction in line with a good quality of stability aspect is necessary to be attained. Therefore, a comparative study of two common solution methods, namely conventional cantilever wall and mechanically stabilized earth wall, was conducted to determine the best solution for slope failure remediation in the case studied. The analysis was performed by using a computer software program coded Geo5. A slope failure case in Bali was selected to investigate the performance of both studied methods in meeting all engineering criteria, including bearing capacity, internal stability (overturning and sliding), and global stability. The results show that mechanically stabilized earth wall gives more advantage not only in meeting all criteria but also in providing aesthetic concern and sustainable performance. On the other hand, conventional cantilever walls show a deficiency in global stability that will require pile foundation support or another reinforcement under the base plate, which will automatically increase construction time. The use of computer software will provide a more sophisticated analysis to examine various slope failure remediation methods to establish the most suitable solution for the specific sites. There is still expansive room to be researched in this area.